2023
DOI: 10.1039/d3nj01840g
|View full text |Cite
|
Sign up to set email alerts
|

Secondary doping of Mn/Co bimetallic ZIF-derived catalysts for the oxygen reduction reaction

Abstract: We report a bimetallic catalyst Mn0.1Co0.3/NC-2, which excellent ORR activity in alkaline and acidic electrolytes, due to the increased number of M–Nx active sites by secondary doping and the synergistic effect of the Mn and Co bimetals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…After ZIF-8 coating, the product presents characteristic diffraction peaks indexed to (011), (002), (112), (022), (013), (222), (233), and (134) planes of ZIF-8 at 7.2°, 10.3°, 12.7°, 14.6°, 16.3°, 18.0°, 24.6°, and 26.6°, respectively. 32,33 This result demonstrates two phases (Fe 3 O 4 -COOH and ZIF-8) in the composite material. The characteristic peaks of Fe 3 O 4 @ZIF-8-CUR are comparable to those of Fe 3 O 4 @ZIF-8, indicating the well-maintained degree of crystallinity of the drug delivery system.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…After ZIF-8 coating, the product presents characteristic diffraction peaks indexed to (011), (002), (112), (022), (013), (222), (233), and (134) planes of ZIF-8 at 7.2°, 10.3°, 12.7°, 14.6°, 16.3°, 18.0°, 24.6°, and 26.6°, respectively. 32,33 This result demonstrates two phases (Fe 3 O 4 -COOH and ZIF-8) in the composite material. The characteristic peaks of Fe 3 O 4 @ZIF-8-CUR are comparable to those of Fe 3 O 4 @ZIF-8, indicating the well-maintained degree of crystallinity of the drug delivery system.…”
Section: Resultsmentioning
confidence: 63%
“…31 It is now well established from a variety of studies that ZIF-8 is recognized as a common nanocarrier for loading medicine, protein, and DNA. 32–34 Curcumol (CUR), a food source compound isolated from herbal medicine plant, has been reported to exert anticancer effects in multiple tumour cell lines without any side effects. 35 Recent research has shown its therapeutic effects such as inducing receptor-interacting PIPK1/PIPK3 through the JNK-ROS pathway and suppressing hepatocellular carcinoma cell growth, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Metal atoms doping provides a unique platform for studying catalytic reactions with enhanced activity and durability. ,,, The findings demonstrate that Mn–N–C involved with bimetallic atoms substantially enhances electrocatalytic performance compared to Mn–N–C with monometallic atoms. ,, Moreover, the collaborative influence of the two metallic components markedly enhances catalytic efficiency and stability by facilitating electron transfer pathways and distribution. ,, Given the various electronegativity of metal atoms, doping additional metal atoms and N atoms can change the electronic configuration near the carbon framework, improving specific adsorption-free energy of reactants. ,, Consequently, incorporating two metal atoms with distinct catalytic benefits into N-doped carbon materials, uniformly dispersed by the same atom, yields high-performance bimetal electrocatalysts. , Recently, researchers have investigated the introduction of additional transition metal atoms into Mn–N–C to form bimetallic-doped carbon materials, which can alter the electronic configuration of Mn sites and reconfigure unique active sites that differ from monometallic Mn–N–C catalysts. , Additionally, the collaborative influence of bimetal can reduce the energy barrier for ORR and expedite charge transfer, thus improving ORR catalytic process. ,, …”
Section: Mn–n–c Electrocatalyst For Orrmentioning
confidence: 99%
“…Guo et al introduced a bimetallic catalyst through a secondary doping approach and prepared the carbon catalyst codoped with Mn and Co (Mn 0.1 Co 0.3 /NC-2) (Figure a). XPS analysis confirmed the existence of Mn and Co (Figure (b-c)).…”
Section: Mn–n–c Electrocatalyst For Orrmentioning
confidence: 99%
See 1 more Smart Citation